Can the use of magnetized water affect the seedling development and the metabolite profiles of two different species: Lentil and durum wheat? - Sestili, Sara; Platani, Cristiano; Palma, Daniela; Dattoli, Maria Assunta; Beleggia, Romina (Frontiers in Plant Science, 2023)
The influence of magnetic water on plant development and metabolic profile was investigated. The efficiency of this novel technology on roots and epicotyls elongation of durum wheat and lentil plantlets was tested. The magnetic treatment device was used to flow out tap water through a magnetic field of max. 12900 - 13200 Gauss (G) ﬂow rate. Seeds and plantlets were grown on a sand-free paper soaked by magnetized and tap water as control. The growth parameters were collected at three-time points (48, 96 and 144 hours after treatment) at which the metabolomic analysis were also performed. Although the effect varied with the species, tissues and time points considered, compared with Tap water (TW), the use of magnetic water treated (MWT) led to higher root elongation in both genotypes. On the contrary, the epicotyl length was not affected by treatment both in durum wheat and lentils. The results indicate that the use of magnetized water in agriculture can be considered a sustainable technology to promote plant development and quality with a reduced and more efficient water usage leading to cost saving and environmental protection.